Novel Fluorescent Fluorene-Containing Conjugated Polymers: Synthesis, Photophysical Properties, and Application for the Detection of Common Bisphenols - Jones, Daniel R.; Vallee, Ryan; Levine, Mindy (Synlett, 2018)
Eight new fluorescent conjugated polymers were synthesized by the Suzuki polycondensation reaction of 9,9-dioctylfluorene-2,7-diboronic acid bis(1,3-propanediol) ester and a conjugated dihalogenated monomer. The photophysical properties of these polymers were investigated as well-dissolved solutions in chloroform and as nanoparticle suspensions in water. Several of the polymers had large Stokes shifts (greater than 100 nm) and others demonstrated unique changes in the fluorescence properties in aggregated verse nonaggregated forms. Preliminary applications of these polymers in the detection of common bisphenols are also reported.
Keywords: polymers; nanostructures; aggregation; spectroscopy; conjugation